2019
DOI: 10.1302/1863-2548.13.180165
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between ultrasonic and radiographic imaging of developmental dysplasia of the hip

Abstract: Purpose The correlation between the degree of developmental hip dysplasia (DDH) measured on ultrasound images compared with that measured on radiographs is not clear. Most studies have compared ultrasonography (US) and radiographic images made at different times of follow-up. In this study the correlation between US images and radiographs of the hip made on the same day was evaluated. Methods US images and radiographs of both hips of 74 infants, who were treated for stable DDH, were reviewed in a retrospective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 22 publications
2
15
0
Order By: Relevance
“…Spaans et. al analyzed US and XR performed on the same day in 74 infants being treated for stable DDH [24]. Counter to our results, they found that US was able to diagnose DDH in more hips than XR.…”
Section: Discussionsupporting
confidence: 71%
“…Spaans et. al analyzed US and XR performed on the same day in 74 infants being treated for stable DDH [24]. Counter to our results, they found that US was able to diagnose DDH in more hips than XR.…”
Section: Discussionsupporting
confidence: 71%
“…A few studies have compared ultrasound and radiographs in infants. 16 As shown in Legg-Calvé-Perthes disease, ultrasound is able to detect transient synovitis and an irregular contour of the femoral head. In patients with fragmentation, the altered bone structure is visualized.…”
Section: Discussionmentioning
confidence: 98%
“…However, there are disadvantages to radiography for the evaluation of DDH, including the risk of radiation and that only bony structures can be seen. In the first months of life, most bony parts of the femoral head and acetabulum remain cartilaginous, which limits the use of plain radiographs for the diagnosis in infants younger than 6 months (2). Therefore, hip sonography has become important in diagnosis, especially in the first six months of an infant's life.…”
Section: Introductionmentioning
confidence: 99%